Narrative, ideology and political effect in PERSEPOLIS - Ruiz Dodobara, Rosa (2016)
The present study analyzes Persepolis (2000), the autobiographical comic by the Iranian Marjane Satrapi (1969). The play was awarded the prize to the Best Screenplay in Angoulême in 2002, which is one of the largest comics festivals worldwide. The story was subsequent- ly adapted into a film and won the Special Jury Prize of Cannes Film Festival in 2007. The play is an effort to rebuild the life of the author, her autobiography, which is delimited in the modernism and postmodernism during 1979 to 1994. That was the period where she spent her childhood, adolescence and youth in the middle of the controversial political context of her country, Iran, and also included her stay of three years in Vienna.